Sistem Pakar Untuk Mendiagnosa Tingkat Stres Karyawan PT ACE Hardware Indonesia Tbk Dengan Menggunakan Metode Certainty Factor (CF) - Purnama Djati, Widya; Gultom, Herwis (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Stress is a mental disorder that is commonly experienced by employees of PT ACE HARDWARE INDONESIA Tbk. Most of the stress that occurs is often considered trivial, and if the stress is not handled immediately it will get worse and will affect productivity at work which will cause a decrease in turnover for PT ACE HARDWARE INDONESIA Tbk. So therefore we need a tool or system that has the ability like a psychologist in diagnosing this level of stress. The system is an expert system that solves problems as is usually done by experts. This study aims to create an expert system application for stress diagnosis. This system application diagnoses stress levels with the Prototype and the Certainty Factor method. The Certainty Factor method is a method for proving whether a fact is certain or uncertain. This method provides space for experts to give confidence in the knowledge they have. From calculations using the Centainty Factor method at each level, from the symptoms that employees input for mild stress levels the probability is 0.92% or 92%, while the symptoms inputted by employees for moderate stress levels are likely to be 0.994624 or 99.46%, from the results of the comparison of these possibilities the maximum value of CF is 0.994624 or 99.46% with a moderate stress level.